Single Case Experience of Immunosuppressant Administration to SystemicSclerosis-ILD Patients with Aspergilloma - Wilujeng Anggraini (Indonesian Journal of Rheumatology, 2022)
Background: Systemic sclerosis (SSc) is a chronic autoimmune disease thatstill poses a great challenge to clinicians. SSc is characterized by immunedysregulation and progressive fibrosis that typically affects variable internalorgan involvement such as lungs. Interstitial lung disease (ILD) is a commonmanifestation of SSc and a leading cause of death. The immunosuppressivedrug is the main treatment to suppress the inflammation process in SSc.Case presentation: In this case we report a 40-year-old female to suffer ILDSSc. According to High-Resolution Computed Tomography (HRCT) thorax,we found that it was interstitial lung disease with aspergilloma. She gotmethylprednisolone 3x8 mg and azathioprine 2x50 mg. At the end of thetreatment, the patient showed improvement in her clinical condition andshowed no worsening condition in the HRCT evaluation for her fungalaspergilloma. Conclusion: Systemic sclerosis (SSc) is a rare autoimmunedisease involving the skin and internal organs. The immunosuppressiveagent is still the drug of choice for most autoimmune diseases.Immunosuppressive may promote fungal growth and have been associatedwith increased risk in most serious fungal diseases including aspergilloma.